The level of understanding regarding balanced scorecard in Human Resource Management Chief Minister Department Sarawak / Syed Ismail Wan Drahman - Wan Drahman, Syed Ismail (2013)
Above all I would like to thank The Almighty God for wisdom and blessing for me to complete my practical report successfully. Without the blessing, I would never complete this practical report on time that given to me. Besides that, I would also like to thank our supervisor Madam Arenawati Sehat binti Omar for guiding, give support and advise me to complete this study which is ‘The level of Understanding regarding Balanced Scorecard in Human Resource Management, Chief Minister Department Kuching’. In addition, I would like to thank all the parties who are directly and indirectly involve in my practical report and giving full co-operation and information. Thank you also to the respondents that answering our questionnaires because the questionnaires also are part of my practical training requirement and my classmates that help me to use SPSS software to make analysis for the answer of questionnaire. For the parties we did not mention same gratitude for to you all. Before I finish, I like to thank my family and friends for all supports and assistance provided. All of your supports turned me speechless. With a lot of gratefulness, thank you very much.